A customized bed based stand alone array of optically pumped magnetometers for fetal magnetocardiography measurements - Diana Escalona-Vargas; Alberto Ramirez; Eric R. Siegel; Elijah H. Bolin; Hari Eswaran (Scientific Reports)
Abstract Fetal magnetocardiography (fMCG) is a non-invasive technique that measures the magnetic fields associated with fetal heart electrical activity outside of the maternal abdomen. fMCG has high temporal precision for measuring fetal heart rate and its variability which reflects fetal neurodevelopment. Free of cryogenics and low-cost sensors called microfabricated optically pumped magnetometers (OPMs) have emerged as an alternate to cryogenic SQUID (Superconducting Quantum Interference Device) systems to record fMCG. Previous research has demonstrated the ability of the OPMs to measure the fMCG at different maternal positions by taking the advantage of the conformal and geometric flexibility of the sensors. In this work, we designed and configured a bed-based stand-alone array of OPMs to obtain serial recordings of fMCG. 72 combined OPM-SQUID recordings were conducted at different gestational ages in 22 pregnant women. We were able to obtain fMCG with similar detectability as the gold standard SQUID from OPM sensors mounted on a novel belly-shape patient interface design with movable sensor holders. While additional translational research is needed, the outcome of this study can further facilitate the development of a non-cryogenic low-cost smaller footprint device to increase the use of OPMs for fetal research and clinical applications.